Recidivas e recorrências de carcinomas basocelulares da face - Ocanha, Juliana Polizel [UNESP]; Dias, Juliana Tedesco [UNESP]; Miot, Hélio Amante [UNESP]; Stolf, Hamilton Ometto [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP] (Sociedade Brasileira de Dermatologia, 2011)
Para avaliar fatores relacionados ao seguimento oncológico dos carcinomas basocelulares da face, foi realizada a análise de série de casos. Avaliaram-se 465 pacientes, com 834 carcinomas basocelulares de face; 3,1% apresentaram recidivas. Nos tumores incompletamente excisados, a recidiva foi 14,7% contra 2,3% dos tumores, com margens livres. Ocorreram mais na região nasal. As taxas de recorrência evidenciaram risco cumulativo. Estes achados reforçam a importância do seguimento oncológico após a cirurgia do carcinoma basocelular.

To evaluate factors related to oncological follow-up of basal cell face carcinomas it was carried out the analysis of a series of cases. Four hundred sixty-five patients with 834 basal cell face carcinomas were evaluated; 3,1% presented recurrences. There was 14.7% of recurrence in incompletely excised tumors against 2.3% of the tumors with clear margins. Recurrences were more prevalent on the nose. Relapse rates showed a cumulative risk. These findings reinforce the importance of oncological follow-up after surgery of basal cell carcinoma.
Relapses and recurrences of basal cell face carcinomas
Keywords: Carcinoma basocelular; Cirurgia geral; Neoplasias cutâneas; Patologia; Recidiva local de neoplasia; Carcinoma, basal cell; General surgery; Neoplasm recurrence, local; Pathology; skin neoplasms